Betatron radiography and tomography of steel castings with large thickness; MATEC Web of Conferences; Vol. 158 : Space Engineering - Kayralapov D. Daniyar; Zhong Yang; Batranin A. V. Andrey Viktorovich; Chakhlov S. V. Sergey Vladimirovich (2018, 2018)
Title screen